Effect of alloying elements on austenite grain growth and microstructure refinement in a non-quenched steel for crankshafts - ZHANG Chao-lei; YANG Zhong; SUN Jing-hong; ZHAO Hai-dong; LI Bo-yuan; LIU Ya-zheng (工程科学学报, 2015)
The microstructural refinement effect of alloying elements Nb, Ti and S was investigated by analyzing austenite grain growth behavior and hot-rolled microstructure in a non-quenched steel for crankshafts. The results show that the austenite grain coarsening temperature increases by 100℃ when the heating time is 30 min, and the microstructure in the hot-rolled bar edge is significantly refined after 0.027% Nb-0.012% Ti microalloying and an increase of S from 0.029% to 0.046% in the steel investigated. The undissolved second phase particles MnS and (Nb, Ti) (C, N) have a pinning effect on austenite grain boundaries, and then retard the austenite grain growth. Besides, the microstructural refinement effect of the alloying elements needs a suitable deformation schedule.